Problem Solving Profile of Students with High Self-Efficacy Levels in terms of Gender - Reni Kurnia Putri; Firda Hariyanti (JME (Journal of Mathematics Education), 2022)
This research is motivated by the low mathematical problem-solving ability of MTs students. The purpose of the study was to describe the problem-solving profile of students with high self-efficacy in terms of students gender. The research method is qualitative research, where the research subject consists of one male student and one female student with a high level of self-efficacy from MTs students in class VIII-A. The main instrument is the researcher himself, supported by problem-solving tests, selfefficacy questionnaires, and interview guidelines. The data analysis technique was carried out using stages, namely: data reduction, data presentation, and conclusion. The results showed that in solving problems male students with high self-efficacy were superior to female students with high self-efficacy, namely: (1) In The stage of understanding the problem, male and female students with high self-efficacy were able to name all that information known and asked. (2) In the planning stage, male and female students with high self-efficacy are good enough in determining strategies. (3) In the stage of implementing the plan, male and female students with high self-efficacy were following the planned strategy. However, in practice, female students with high selfefficacy make many mistakes, so the results obtained are not correct. (4) In the reexamination stage, male and female students with high self-efficacy re-examine the results of their answers.